MODERN THYROID GLAND DISEASES CLINICAL LABORATORY DIAGNOSTIC METHODS - Kuvandikov G'.B; Mudit Chhajer; Kurbonova L.M (TADQIQOTLAR.UZ, 2024)
In practice, very different laboratory methods are used in the diagnosis of thyroid gland diseases. These consist of several parts: 1. Thyroid hormones and methods for determining the amount of other iodine compounds in the blood: the amount of iodine bound to protein; iodine separated by butanol; total T4, free thyroxine T4; consists in determining the amount of total T3, free T3, reversible T3, thyroxine-binding proteins (globulin and rrealbumin). Methods for determining the functional state of the thyroid gland: the ability of the thyroid gland to absorb J 131; the method transmitted by the effect of triiodothyronine T3, the method transmitted by thyroliberin, the method showing a decrease in the thyroid gland'sability to capture iodine, and so on. Methods of studying the peripheral effects of thyroid hormones, determination of basic metabolism: determination of the amount of creatinine phosphokinase in blood serum; determining the heel reflex time; (photomathography, reflexometry, reflexography), the amount of serum SAMF to glucagon methods that determine the answer.